Recursive trimmed filter in eliminating high density impulse noise from digital image - Yulianto, Ilyasa Pahlevi Reza; Ramadhan, Bima; Abdurrazzaq, Achmad (Desimal: Jurnal Matematika, 2023)
Advances in technology have made it easier to share media over the Internet. In the process of media sharing, a media may receive noise or interference that results in loss of information. In this paper, a new method to remove Salt and Pepper noise from images based on recursive method will be presented. The first stage is to recognize the noise from the damaged image, the damaged pixels will be replaced by the mean of the surrounding window, the difference with other methods is the use of recursive approach that aims to minimize the size of the window in the recovery process.